Pengaruh Konseling Laktasi Intensif Terhadap Keberhasilan Pemberian Air Susu Ibu (ASI) Eksklusif Sampai 6 Bulan Di Kelurahan Kudu Kecamatan Genuk Kota Semarang - Emi Sutrisminah; Isna Hudaya (INVOLUSI: Jurnal Ilmu Kebidanan, 2020)
In 2018, the coverage of exclusive breastfeeding in Semarang City was 68.22%, one of the causes was the lack of lactation counseling by health personnel, and the low behavior of breastfeeding mothers to exclusively breastfeed. Objective: To determine the effect of intensive lactation counseling on exclusive breastfeeding for up to 6 months. The research design used was a “quasi-experiment with posttest-only non-equivalent control group design”. Sampling technique was used for sampling with a total sample size of 60 respondents in each group. Bivariate analysis used a chi square with a significance level of p <0.05. The results showed that there was a significant difference in knowledge after lactation counseling was carried out in the intervention group (p value 0.004 <0.05, there was a significant difference in success in giving ASI between the intervention group and the control group after counseling (p value 0.008 <0.05; RR 2.500). Lactation counseling has an effect on knowledge and the success of giving breastfeeding.